2000
DOI: 10.1007/s004310050050
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the choline content of human breast milk in the first 3 weeks after birth

Abstract: The choline content of human breast milk doubles 6-7 days after birth and, unlike that of many formula feeds, appears to be sufficient to account for betaine excretion in healthy full-term neonates. However, for premature babies who usually receive much lower quantities of milk, yet have a higher demand for choline, the intake may be inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 20 publications
12
41
2
1
Order By: Relevance
“…The observed significant positive correlations between breast milk free choline levels and serum free choline, phospholipid-bound choline and glycerophosphocholine concentrations indicate that circulating choline status can influence the milk content of free choline. Previous studies have clearly shown that the choline contents and compositions of infant formulas and mature human breast milk are different [19,36], and oral bioavailability of choline compounds varies considerably [43]. Our present data are in good accordance with these previous findings and show that the serum free choline concentration in formula-fed infants is significantly lower than the serum free choline concentrations observed in breast-fed infants ( Table 4).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…The observed significant positive correlations between breast milk free choline levels and serum free choline, phospholipid-bound choline and glycerophosphocholine concentrations indicate that circulating choline status can influence the milk content of free choline. Previous studies have clearly shown that the choline contents and compositions of infant formulas and mature human breast milk are different [19,36], and oral bioavailability of choline compounds varies considerably [43]. Our present data are in good accordance with these previous findings and show that the serum free choline concentration in formula-fed infants is significantly lower than the serum free choline concentrations observed in breast-fed infants ( Table 4).…”
Section: Discussionsupporting
confidence: 95%
“…Our data for the total choline content of the colostrum (706 Amol/L) are also in agreement with those (0.60 mmol/L) of Holmes et al [36]. Holmes et al [36] found that the total choline content and levels of free choline, phosphocholine and glycerophosphocholine in human breast milk rise considerably between 7 and 22 days after birth [36]. In accordance with this finding, we found that the levels of free choline, phosphocholine and glycerophosphocholine in breast milk, expressed between 12 and 28 days after birth, were two, three and five times higher than the observed values for the colostrums (0-2 days after birth), respectively.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Both forms of choline were found to be doubled in breast-feeding women 12-28 post-partum. In an earlier study, it was determined that the total choline content in human colostrum is lower than in mature milk seven days post-partum, which coincides with the acceleration in growth in neonates at this stage (Holmes et al, 2000). Choline is an important metabolite for infant development due to its role in brain development and function (Zeisel et al, 1994).…”
Section: Impact Of Breastmilk On Infant Health Outcomesmentioning
confidence: 99%